Evaluation of sampling systems in iron ore concentrating and pelletizing processes – Quantification of Total Sampling Error (TSE) vs. process variation. (15th January 2018) - Engström, Karin; Esbensen, Kim H.
Highlights: Regular control of sampling variability through variographic characterization. Variographic analysis of process data enable evaluation of sampling systems. Variographic analysis of sampling systems can replace precision experiments. Periodicity and changes in process variation can be detected and counteracted early. Result show significant benefits with variographic analysis of industrial processes. Abstract: Process sampling is involved in grade control in all parts of the production value chain in mineral processing. Reliable sampling and assaying is essential to ensure final product quality, but the need for representative sampling is not always taken into account. By continuous control of the variability of sampling systems, a comprehensive understanding of the relationship between the sampling and process variability can lower the risk for overcorrections of process parameters due to sampling variability rather than process changes. Variographic characterization of process sampling makes it possible to assess all combined sampling and analytical errors from only 40–60 routine analytical values. The objective of this study is to evaluate total sampling variability in relation to process variability in the concentrating and pelletizing process sampling at LKAB. The results from the variographic analyses will form a basis for suggestions of possible improvements. The results show that variographic analysis is a powerful tool to evaluate both process variations and the variability of the sampling systems employed. The extensive access to time series data allow variographic characterization (quality control) of all critical measurement systems and locations. At the same time, periodicity and small changes in process variation can be detected and counteracted early, minimizing the risk for producing products out of specification.